Optimizing Swallow's Nest Tax: Potential, Effectiveness, and Its Role in Regional Economic Development - Indaliana, Indaliana; Paranoan , Selmita (International Journal of Economics Development Research (IJEDR), 2025)
The swallow's nest tax holds significant potential to enhance Regional Original Revenue (PAD), particularly in Parigi Moutong Regency, where the swallow's nest industry has experienced rapid growth. However, despite its high potential, actual tax revenue remains relatively low. This study aims to analyze the potential, effectiveness, and contribution of the swallow's nest tax to regional tax revenue in Parigi Moutong Regency. A quantitative descriptive approach is used, incorporating documentation studies, field studies, and literature reviews. Data sources include tax revenue reports from the Regional Revenue Agency (BAPENDA) of Parigi Moutong Regency. The potential tax revenue is estimated based on the number of entrepreneurs, production volume, and selling price of swallow's nests. Tax effectiveness is measured by comparing actual revenue with the set target, while tax contribution is assessed based on its proportion to total regional tax revenue. The findings indicate that the swallow's nest tax potential in Parigi Moutong Regency is substantial, with estimated revenues reaching Rp. 7,824,600,000.00 if all taxpayers comply with regulations. The tax collection effectiveness was relatively high between 2020 and 2022, with percentages approaching or exceeding 100%. However, in 2023, effectiveness significantly declined to 67.53%. Despite its potential, the contribution of the swallow's nest tax to total regional tax revenue remains minimal, averaging only 0.21% from 2020 to 2023. In conclusion, while the swallow's nest tax presents a promising revenue source, its realization remains suboptimal due to challenges in taxpayer compliance and low revenue targets. This study highlights the need for enhanced supervision, increased taxpayer awareness, and stricter enforcement policies to maximize swallow's nest tax revenue and strengthen its contribution to the PAD of Parigi Moutong Regency.